2014
DOI: 10.3892/mmr.2014.2547
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of heat shock factor 1 transcription activity is associated with hepatocellular carcinoma progression

Abstract: Heat shock factor 1 (HSF1) is associated with tissue-specific tumorigenesis in a number of mouse models, and has been used a as prognostic marker of cancer types, including breast and prostatic cancer. However, its role in human hepatocellular carcinoma (HCC) is not well understood. Using immunoblotting and immunohistochemical staining, it was identified that HSF1 and its serine (S) 326 phosphorylation, a biomarker of HSF1 activation, are significantly upregulated in human HCC tissues and HCC cell lines compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
18
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 40 publications
3
18
0
Order By: Relevance
“…In our previous study, we found that HSF1 promoted invasion and metastasis of HCC cells and was associated with a poor prognosis for HCC patients (31). Currently, more and more studies have confirmed the important role of HSF1 in tumor progression of HCC (32)(33)(34). Here, we have proven that HSF1 may bind to À1,287$À1,263 site before transcriptional start site of miR-487a and mediate its expression.…”
Section: Discussionmentioning
confidence: 51%
“…In our previous study, we found that HSF1 promoted invasion and metastasis of HCC cells and was associated with a poor prognosis for HCC patients (31). Currently, more and more studies have confirmed the important role of HSF1 in tumor progression of HCC (32)(33)(34). Here, we have proven that HSF1 may bind to À1,287$À1,263 site before transcriptional start site of miR-487a and mediate its expression.…”
Section: Discussionmentioning
confidence: 51%
“…Under physiological conditions, HSF1 protects organisms and cells from various types of stress, such as heat, ischemia, oxidative stress, and other noxious conditions (Vihervaara and Sistonen, 2014). Several studies have demonstrated that HSF1 is activated and predicts a poor prognosis in various types of cancer, including breast cancer (Santagata et al, 2011), colon cancer (Jacobs and Marnett, 2009), and liver cancer (Li et al, 2014b). In cancer cells, HSF1 could drive a transcriptional program that is vital for supporting the malignant state of cancer, and the transcriptional program was highly enriched in protein translation, RNA binding, metabolism, and cell adhesion (Mendillo et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…HSF1 facilitates survival in response stressors by regulating various cellular processes, such as cell-cycle control, protein translation and glucose metabolism (6,7). The expression of HSF1 is reportedly upregulated in cancer cell lines and cancer tissues of hepatocellular carcinoma, and high expression of HSF1 is associated with a poor prognosis in breast cancer and hepatocellular carcinoma (8,9). However, the role of HSF1 as a prognostic biomarker in ESCC has not been well investigated.…”
Section: Introductionmentioning
confidence: 99%